2023
DOI: 10.1259/dmfr.20220209
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the separated root canal instrument on panoramic radiograph: a comparison of LSTM and CNN deep learning methods

Abstract: Objectives: A separated endodontic instrument is one of the challenging complications of root canal treatment. The purpose of this study was to compare two deep learning methods that are convolutional neural network (CNN) and long short-term memory (LSTM) to detect the separated endodontic instruments on dental radiographs. Methods: Panoramic radiographs from the hospital archive were retrospectively evaluated by two dentists. A total of 915 teeth, of which 417 are labeled as “separated instrument” and 498 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to a recent study, Mask R‐CNN could detect pulp stones on bite‐wing radiographs detection with approximately 90% sensitivity [37]. Another recent study showed that CNN models are successful at detecting separated endodontic instruments in panoramic radiographs [13]. The relatively lower accuracy rates compared to our study may be due to the use of panoramic radiographs instead of periapical radiographs and the use of different deep‐learning methods.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…According to a recent study, Mask R‐CNN could detect pulp stones on bite‐wing radiographs detection with approximately 90% sensitivity [37]. Another recent study showed that CNN models are successful at detecting separated endodontic instruments in panoramic radiographs [13]. The relatively lower accuracy rates compared to our study may be due to the use of panoramic radiographs instead of periapical radiographs and the use of different deep‐learning methods.…”
Section: Discussionmentioning
confidence: 56%
“…[8] Periapical lesion detection, evaluation of tooth morphology and root fracture were evaluated using a CNNbased algorithm in dentistry [9][10][11][12]. A recent study also utilised CNN to detect separated endodontic instruments on panoramic radiographs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural network was characterized with high levels of accuracy and sensitivity (84.37 ± 2.79 and 81.26 ± 4.79 correspondingly) for the detection of broken endodontic fi le within the root canal based on the panoramic images analysis [21]. Analogically AI helped to predict presence of C-shaped distal canal within mandibular molar based on the analysis of panoramic images with the accuracy of 95.1% and sensitivity of 92.7% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of panoramic pictures using a convolutional neural network has been shown to be highly accurate and sensitive (84.37 ± 2.79 and 81.26 ± 4.79, respectively) for detecting a damaged endodontic file within the root canal [40].…”
Section: Ai In Endodonticsmentioning
confidence: 99%